Creating a New Normal Through Engagement in Meaningful Occupation - Jennifer Fortuna (Scholarworks @ WMU, 2021)
Katie Edick, an occupational therapist and artist based in Portland, Michigan, provided the cover art for the Winter 2021 edition of The Open Journal of Occupational Therapy (OJOT). "Katie Bird" is a 4" x 6" watercolor painting. After receiving a diagnosis of metastatic breast cancer (MBC), Katie set out to find a new purpose and leave a legacy. She made the decision to live with intention and choose life experiences that create joy. Through engagement in meaningful occupations, such as painting and patient advocacy, Katie is creating a new normal.